Parental Negligence on Narcissism and Aggression Among Young Adults - Goel, Kanishka; Pandey, Neelam (Journal of Commerce and Trade, 2018)
Negligence means when parents brought up their child in the sense that endangers the health and life of their child. Parents are not able to take necessary steps and make proper decisions for them while rising up their child.. These forms of negligence are leaving a child alone when he or she needs protection or parents are unable to provide food, clothing, not able to pay medical attention or education to a child, or placing the child in harmful or dangerous circumstances abusive or sexually predatory person including exposing the child to a violent. The aim of the study was to study parental negligence on narcissism and aggression among young adults. The sample of the study was total of 120 subjects between the age group of 18 to 22 randomly selected from Delhi, Noida, and Meerut. The tools selected were a checklist for measuring parental negligence, Narcissistic Personality Inventory and Buss- Perry Aggression Questionnaire. The study conducted was to understand parental negligence will impact narcissism and aggression. The findings of the study show that parental negligence impacts the narcissistic personality and aggression among young adults. The suggested reason for this finding can be that when children gets neglected their basic needs such as clothing, education, basic nutritional level etc. are not met which creates tuffel in their mind and nature creating frustration which causes aggression. Classification-JEL : I21, J17